Being Pious Among Indonesian Salafists - Wahib, Ahmad Bunyan (Al-Jamiah Research Centre, 2017)
This essay is a brief explanation on the development of the process of Islamic Puritanism among Salafis in Indonesia. The article argues that the Salafis in Indonesia are in the process of puritanization and Arabization. Being pious, to them, means that one has to become an Arab and a Puritan Muslim. This puritanization of Islam is shown by purifying Islamic doctrines from any deviation. That is, religious concepts and practices should be based on the Qurâan and the Sunna only. Likewise, Salafis present themselves as like Arabs as their men let their beard grows, wear turban and trousers above their ankles, while their women wear enveloping veil (niqab). The research also found out that the using of Arabic words, like abi (father), umi (mother), âami (uncle), âama (aunt), akhi and ukhti for friend, are widely popular. Changing name from Javanese to Arabic is another form of Arabization. The acts of piety among Indonesian purist Salafis show that Salafi challenges both secular and traditional worlds which aim to create a stronger bonding every the followers among them, but, at the same time, distance them from other groups.[Tulisan ini menjelaskan tentang perkembangan proses puritanisasi diantara kaum Salafi di indonesia. Tulisan ini memberikan argumen bahwa anggota gerakan Salafi sebenarnya mengalami puritanisasi dan arabisasi. Mereka beranggapan bahwa menjadi orang baik dan saleh berarti menjadi seperti orang Arab dan muslim yang puritan dengan jalan memurnikan doktrin agama dari penyimpangan-penyimpangan. Cara yang diambil adalah dengan kembali kepada Al Qurâan dan As Sunnah. Misalnya bagi laki-laki salaf adalah menumbuhkan jenggot, menggunakan surban dan memakai celana yang panjangnya di atas mata kaki. Sedangkan bagi perempuan harus menggunakan jilbab. Selain itu penelitian ini juga menemukan populernya penggunaan nama panggilan yang berasal dari bahasa Arab, seperti abi, umi, ami dan ama diantara mereka sendiri. Ada juga kecenderungan pergantian nama Jawa menjadi nama Arab. Kesalehan mereka sebenarnya ditujukan untuk merespon tradisionalitas dan modernitas, akan tetapi disaat yuang sama mereka justru membuat jarak dengan kelompok yang lain.]